Hubungan Antara Pola Asuh Ibudengan Perkembangan Personal Sosial Anak Usia Prasekolahdi Kelompok Bermainbaiturrahmankarangasem - Lahemma, Ashari; Susilaningsih, Endang Zulaicha Susilaningsih, S.Kp.,M.Kep (2016)
The development aspect of children at preschool is important aspect which needs to be optimalized especially social personal. The development of children's social personal can be seen in socialization, interaction, and independence of the children. Many factors influence the development, one of the fundamental is parenting. The objective of this research is to know the corelation between mother's parenting and personal social development of preschool children in playgroup Baiturrahman Karangasem. The kind of this research uses analitic observational design and cross sectional approaching. The technique of taking sample used is non probability technique. It is total sampling. The sample consists of 48 respondents which are preschool children in playgroup Baiturrahman Karangasem and some their mothers. The tabulation data uses Spearman Rank analysis.The result of the univariate analysis shows the data as much 60,4% of parenting applied by the mothers is democratic and 68,7% of children social personal development is normal. The result of calculation corelation Spearman Rank shows p value (0,003) < α (0,05). It means there is corelation between mother's parenting and personal social development of preschool children in playgroup Baiturrahman Karangasem. The suggestion to the next research needs to concern others factor which influence the development of children personal and mother's parenting. Keyword : Mother's parenting, preschool, social personalBiblliography : 36 (2006-2016)